How to Identify Misconception Using Certainty of Response Index (CRI): A Study Case of Mathematical Chemistry Subject by Experimental Demonstration of Adsorption - Putri, Silmi Ridwan; Hofifah, Siti Nur; Girsang, Gabriela Chelvina Santiuly; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Multidiciplinary Research, 2022)
The purpose of this study was to identify misconceptions using the certainty of response in undergraduate students through a case study of mathematical chemistry subject by experimental demonstration of adsorption. The concept of mathematical chemistry was conveyed to students by using an explanation video. The video also directs students to do practical experiments on adsorption. The data obtained can be used to determine the isotherm adsorption model that fits with their experimental phenomena. Students analyze the data obtained by using their understanding of the mathematical chemistry concepts that have been taught. Misconceptions on students were analyzed using pretest-posttest by giving 20 questions followed by the guess level (CRI). Based on the answers given, students' understanding of the concepts being taught can be identified as understanding the concept, lucky guess, do not understand the concept, and misconceptions. This research can be used as a reference to identify misconceptions in students and can be applied in various subjects.